2022
DOI: 10.1097/jxx.0000000000000735
|View full text |Cite
|
Sign up to set email alerts
|

She came to me for care, why would I say no? Survey results of advanced practice nurses caring for transgender and gender diverse patients

Abstract: Background: Literature has recognized deficient knowledge of transgender or gender diverse (TGD) patient needs that can negatively affect health care. Prior research on education has shown little progress responsive to TGD health care needs from nursing. Findings from this demonstrate some improvement, however slight. This study examined the education of family nurse practitioners (FNPs) providing care to TGD patients. Purpose:The purposes of this study were to describe the relationship between location of pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Integrating the knowledge learned into the clinical setting, and continuing to practice health history-taking skills, likely benefitted the clinical skill development. Klotzbaugh et al (2022) found that most NPs working with TGD patients have learned best practices through continuing education opportunities, and NPs graduating after 2011 are more likely to have received TGD health content in their advanced practice curriculum as compared with NPs who graduated before 2011. This demonstrates a large learning gap among NPs because those who are considered most experienced in the field may lack this area of training.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Integrating the knowledge learned into the clinical setting, and continuing to practice health history-taking skills, likely benefitted the clinical skill development. Klotzbaugh et al (2022) found that most NPs working with TGD patients have learned best practices through continuing education opportunities, and NPs graduating after 2011 are more likely to have received TGD health content in their advanced practice curriculum as compared with NPs who graduated before 2011. This demonstrates a large learning gap among NPs because those who are considered most experienced in the field may lack this area of training.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, new graduates are ill-equipped in providing GAC. Klotzbaugh et al (2022) surveyed a group of 356 NPs who provide GAC to TGD patients and found that 26.1% of participants received prior education regarding health care needs specific to TGD patients, whereas 25.8% learned physical assessment considerations specific to TGD patients and 6.5% received education specific to providing gender-affirming hormone therapy. For NPs providing GAC to patients, the majority have taught themselves through continuing education on this content because it is not often included in advanced practice NP programs (Klotzbaugh et al, 2022).…”
Section: Background and Purposementioning
confidence: 99%
“…Research examining health care providers’ educational preparation to care for TGE patients has revealed significant gaps. Surveys of family nurse practitioners (NPs; n = 356) and mental health providers ( n = 281) showed that less than 30 percent of respondents in both groups (20%–25% and 26%, respectively) had been offered training about the health needs of TGE people prior to entry into practice (Klotzbaugh et al, 2022; Stryker et al, 2022). Similarly, in a cross-sectional descriptive study of pediatric NPs ( n = 93), the majority believed they had not been adequately prepared to care for TGE youth during their advanced practice education and had to rely on continuing education training to improve their knowledge and confidence (Collins, 2021).…”
Section: Introductionmentioning
confidence: 99%